Analysis Of the Quality of Childcare Services Using the Servqual Method and The Zone of Tolerance Method (Case study: Yayasan Peduli Lingkungan dan Sosial Indonesia) - Suwanto, M; Hidayat, Hidayat; Negoro, Yanuar Pandu (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The purpose of this study is to use SERVQUAL and the Zone of Tolerance methodologies to evaluate daycare facilities. Research was carried out to comprehend the elements that impact the quality of childcare services to enhance the experience and happiness of service users. A quantitative descriptive-analytical technique was used. Questionnaires were sent to parents who used early childhood care programs to gather data. To assess the gap between customer expectations and perceptions of service quality, the obtained data was analysed using the SERVQUAL technique. The Zone of Tolerance approach was also used to estimate the degree of consumer satisfaction with the services delivered. Staff neatness and service costs/tariffs came out positively in the Servqual gap analysis (0.150 and 0.117, respectively). Two positive MMS value characteristics were produced using the zone of tolerance approach. The zone of tolerance encompasses two characteristics: the ability to respond quickly and efficiently while delivering services (0.017, -0.067) and the capacity to meet customers' unique requirements (0.017, -0.100). The sufficient service category includes five service qualities; if any of these are no longer acceptable to clients, the service must be corrected quickly. Keywords: service quality, child care, Servqual, zone of tolerance